Factors affecting healing of rotator cuff repairs: microfracture of the greater tuberosity - Gwan Kyu Son; Myung Seo Kim (Clinics in Shoulder and Elbow)
Background This study aimed to investigate the impact of microfractures generated within the footprint of the greater tuberosity (GT) on postoperative cuff healing following arthroscopic rotator cuff repair (ARCR). Methods A retrospective analysis was conducted on patients who underwent ARCR for full-thickness rotator cuff tear (FTRCT) between April 2020 and October 2023 at our institution. A total of 73 patients was categorized into two groups based on the presence of microfractures: a microfracture group (group M, n=33) and a non-microfracture group (group N, n=40). Six months post-surgery, magnetic resonance imaging was performed to assess cuff healing and retear rates between the two groups. Furthermore, patients were stratified into retear and healing groups based on cuff integrity to analyze the factors influencing retear. Results There was no significant difference in retear rates between groups M and N (18.2% vs. 10.0%, P=0.332). Among demographic factors, age showed a significant difference between the retear and healing groups (67.4±8.5 vs. 61.6±6.1, P=0.044). ML tear size (3.1±1.7 vs. 2.0±1.1, P=0.015), AP tear size (2.4±1.2 vs. 1.6±1.0, P=0.332), FI of the supraspinatus (2.3±1.3 vs. 1.4±1.0, P=0.029), and FI of the infraspinatus (1.6±1.3 vs. 0.9±0.8, P=0.015) exhibited significant differences between the retear and healing groups. Conclusions ARCR with concurrent microfracture of the GT footprint did not significantly impact cuff healing in patients with FTRCT. However, older age and larger ML tear size were associated with an increased risk of retear. Level of evidence III.